A New Biphenyl from Garcinia oligantha and Its Cytotoxicity - Liu, Guiyou; Li, Limei; Wang, Huan; Yang, Juanxia; Lou, Jie; Hu, Qiufen; Ye, Yanqing; Gao, Xuemei (Asian Journal of Chemistry, 2015)
A new biphenyl i.e., 3-methoxy-5-methoxycarbonyl-4-hydroxy-biphenyl (1) was isolated from the stems of Garcinia oligantha. Its structure was elucidated by spectroscopic methods, including extensive 1D- and 2D- NMR. This biphenyl was tested for its cytotoxicity against five human tumor cell lines (NB4, A549, SHSY5Y, PC3 and MCF7) and it showed modest cytotoxicity against SHSY5Y, A549 and MCF7 cell with IC50 values of 7.1, 6.2 and 4.8 μM, respectively.